Computer Application in the Clinical Laboratory - Höhne, K. H.; Dahlmann, K.; Dix, W.-R.; Harm, K. (Methods of Information in Medicine, 1974)
The utilisation of computers in clinical chemistry has decreased administrative overhead and improved the efficiency of the measuring equipment. Supervising physicians can hardly keep up with the increased flow of valuable data. Thus, besides the straightforward data acquisition and reporting of results, the aim of computer application in the clinical laboratory is to make data interpretation more transparent.LABMAT, in addition to acquiring data, offers the possibility of presenting, checking and analyzing the data according to user-selected criteria at any time. The’ system, which has now been in daily operation for over three years, has a satellite structure. A PDP-8/I computer acquires data from 5 measuring devices and can present the results on five terminals or on a typewriter. It is connected by telephone to a large computing center (2 x IBM/370—168) where data storage and retrieval are performed. The structure of the system, examples of its usage and conclusions based on three years experience with daily operation are described.
Keywords: Information System; Clinical Chemistry; On-line Data Acquisition; On-line Data Retrieval; Satellite Computer System